Effect of electroacupuncture on cyclic adenosine monophosphate-protein kinase A-vanillic acid receptor subtype 1 of the transient receptor potential/PLK-protein kinase C-vanillic acid receptor subtype 1 of the transient receptor potential pathway based on RNA-seq analysis in prostate tissue in rats with chronic prostatitis/chronic pelvic pain syndrome - Wu, Xiao-Ling; Cheng, Kai; Xu, Chang; Chai, Ye-Mao; Yap, Tai-Heng; Yang, Zhi-Wen; Sun, Qian-Hui; Tan, Yan; Zhang, Jia-Ni; Chen, Wei; Qiu, Xing-Hua; Yang, Xing-Yue; et al. (Frontiers in Neuroscience, 2022)
Objective: To study the analgesic mechanism of EA on CP/CPPS. Method: 30 male SD rats were randomly divided into three groups with 10 rats in each group: sham group, model group, and the EA group. The CP/CPPS model was established by injecting 50μL of complete Freund's adjuvant into the ventral lobes of the prostate, while the rats in the sham group were injected with the same dose of sterile saline. After 14 days of modeling, in the EA group, “Guanyuan”(CV4) “Zhongji”(CV3) “Sanyinjiao” (SP6) and “Huiyang”(BL35) were punctured (2Hz/100Hz). In the treatment courses, with 40 minutes in each time, once a day, 5 days as a course, 4 courses in total, and rest 2 days between the two courses. After four courses, H&E staining was used to observe the tissue morphology of the prostate in each group; RNA-Seq analysis of differentially expressed genes in prostate of rats in three groups was also performed. GO and KEGG enrichment was analyzed. And finally the signal pathways screened were verified by QRT-PCR. Results: RNA-Seq analysis showed that the number of Pmodel/sham and PEA/model in the prostate was largest, and the intersection between Pmodel/sham and PEA/model was 147. The intersection of GO function between Pmodel/sham and PEA/model was enriched. The biological processes mainly included immune response, inflammatory response, etc; the cell components mainly included plasma membrane, organelle model, and other membrane surfaces; the molecular functions were mainly focused on the functions involved in inflammation and immunity. In the KEGG database, the intersection of signaling pathways between Pmodel/sham and PEA/model was enriched in the NF-kB pathway, cAMP pathway, Phosphatidylinositol pathway, and some immune-related pathways. QRT-PCR results showed that TRPV1, PLC, PKC, cAMP, PKA in the model group was significantly increased compared with the sham group (P<0.01). In the EA group, TRPV1, PLC, PKC, cAMP, PKA was decreased compared with the model group (P<0.05, P<0.01). Conclusion: RNA-Seq could better reflect the differentially expressed genes, and the results were reliable. EA could relieve the pain of CP/CPPS model rats by changing the gene expression in prostate, the mechanism may be related to the cAMP-PKA -TRPV1/PLC-PKC-TRPV1 signal pathway.